Preoperative Total Serum Cholesterol and Patients' Survival in Resected Nonsmall Cell Lung Cancer. (26th November 2012) - Tomita, Masaki; Ayabe, Takanori; Shimizu, Tetsuya; Nakamura, Kunihide
Abstract : The association between hypocholesterolemia and lung cancer risk has been confirmed in some studies. The purpose of the study was to determine whether preoperative hypocholesterolemia (below normal range) is a prognostic factor for survival after nonsmall cell lung cancer (NSCLC) resection. Two hundred and sixty-two consecutive cases of resected NSCLC with a followup period for more than 5 years were reviewed retrospectively. In our results, there were only 13/262 patients having hypocholesterolemia. A significant association was observed between preoperative hypocholesterolemia and patients' survival. However, we failed to find the prognostic significance of preoperative hypocholesterolemia by univariate analysis. No statistical differences were also found by the comparison between 5-year survivors and the others. Our data indicates a trend toward an association between preoperative hypocholesterolemia and poorer survival in NSCLC; however, it did not reach statistical significance.